Online Signature Verification System - Fauziyah, Salehuddin; Mardiana, Bidin; Hazura, Haroon; Zahariah, Manap (2009)
Online signature verification is a process of verifying the writer's identity by using signature verification system. This system can be use as a security system such as verification for assessing entry application and password substitutions. Signature verification technology requires primarily a digitizing tablet and a special pen connected to the universal serial bus port (USB port) of a computer. An individual can sign on the digitizing tablet using the special pen regardless of his signature size and position. The signature is characterized as pen-strokes consisting x-y coordinates and the data will be stored in the signature database in the form of a txt.file. These characteristics uniquely identify a person and cannot be mimicked or stolen. In this project, the method of support vector machine (SVM) is used to focuses in verifying the signature.